Hierarchies and Communication : Analyzing Negotiated Power Relationships in a Small Software Company - Buchko, Robert D. (East Carolina University, 2013)
This dissertation examines chatroom data gathered over the course of approximately five months at a small software organization to determine whether the power hierarchy in such organizations diverges from the org chart bestowed by the organization and, if so, what role communication plays in the formation of the negotiated power hierarchy that emerges instead. The analysis of the data was conducted using three frameworks: Brown and Levinson's Politeness Theory, French and Raven's Bases of Power, and a framework of my own design, Domain / Authority Acknowledgement, which was developed to operationalize the "followership" aspect of power as defined by Holland and Offerman. This dissertation argues that the org chart in such organizations is often a facade, and that analysis using the frameworks listed above allows researchers to identify the true power relationships that exist among the organizations' members.
Keywords: Communication; Business; Behavioral sciences; Authority; Chatrooms; Politeness; Power; Small business--Management; Communication in organizations; Organizational behavior; Hierarchies